Weight estimation of empty carcass and carcass cuts of female SenSi-1 Agrinak chicken - Cecep Hidayat; Sofjan Iskandar (Indonesian Center for Animal Research and Development (ICARD), 2017)
SenSi-1 Agrinak chicken is Indonesian local chicken that was selected for growth rate for six generations. The aim of this study was to estimate of carcass weight and carcass cuts of female SenSi-1 Agrinak chicken, based on age and live weight. The chicks were reared intensively in colony wire cages and they were slaughtered with Islamic method when they reached age of 5, 8 and 15 weeks. Empty carcass and carcass cuts were weight in fresh. Data were analyzed using correlation and regression analysis method. Results showed that the live weight had a high positive correlation to carcass weight and carcass cuts weight of female SenSi-1 Agrinak chickens aged 5, 8 and 15 weeks. Estimation of live weight, carcass, carcass cuts, gizzard, liver and abdominal fat of female SenSi-1 Agrinak, using mathematical model, showed small value differences (0.09 - 4.43%) from the actual data. It was concluded that female SenSi-1 Agrinak chicken’s carcass weight and carcass cuts, could be estimated based on of age in days and live-body weight in gram without slaughtering.